Association of Serotype With Antimicrobial Resistance Patterns Among Shigella flexneri Isolates From Pakistan: The Importance of Serotype 2b. Issue 11 (November 2020) - Nisa, Iqbal; Haroon, Mohammad; Qasim, Muhammad; Driessen, Arnold; Nijland, Jeroen; Yasin, Nusrat; Jalal, Abdullah; Ali, Nawab; Ullah, Waheed; Khan, Taj Ali; Begum, Asia; Rahman, Hazir
Abstract : Background: Shigella flexneri is an emerging threat in low socioeconomic countries including Pakistan. No previous data is available on the association between S. flexneri serotypes and antimicrobial resistance in Pakistan. Objectives: The objective of the present study was to assess the association between serotypes and antimicrobial resistance patterns among S. flexneri isolated from clinical and nonclinical samples. Methods: A total of 199 S. flexneri isolates were subjected to molecular serotyping and antibiotic resistance. Results: The most prevalent S. flexneri serotype was 2b (38%) followed by 1b (24%), 7a (20%), 2a (11%), 1d (5%) and Y (2%). The phylogenetic reconstruction showed 12 clades among which the clades II, III, V, VIII, IX and XI have consisted of serotypes that were found both in human population and environment samples. A high level of multidrug resistance (MDR) was observed in serotype 2b (37.68%) followed by 1b (19.5%) and 7a (19.5%), 2a (11.5%), 1d (5%) and Y (2%). All isolates of serotype 2b showed high level of resistance to amoxicillin/clavulanic acid (100%) followed by quinolone (74.6%) and trimethoprim-sulfamethoxazole (54.6%). Interestingly, none of the serotype was resistant to piperacillin-tazobactam, imipenem and amikacin. The most frequently detected resistance genes among serotype 2b were bla OXA (100%) followed by qnrS (88%), cat (81%) and sul2 (63%). Conclusion: The most frequent S. flexneri serotype was 2b while 1d and Y was first time reported in Pakistan. High frequency of MDR serotypes of S. flexneri is a serious threat in diarrhea endemic regions and thus require urgent strategies for its continuous monitoring and prevention. Abstract : Supplemental Digital Content is available in the text.